Assessing the effectiveness of MISHEQA for internal quality assurance: a multi-stakeholder evaluation - Rosita, Lenny; Tileng, Kartika Gianina; Mardhiana, Hawwin; Christi, Vanessa (Jurnal Mantik, 2025)
The Higher Education Service Institutes (LLDIKTI) Region VII in Indonesia oversees quality assurance for 334 private higher education institutions (HEIs) in East Java. In 2019, it launched the MISHEQA system to support reporting of Internal Quality Assurance System (IQAS) implementation. However, a major issue arose: 26% of HEIs (88 out of 334 institutions) did not report their IQAS data through MISHEQA in 2021, showing a significant increase compared to 11% (35 out of 318 institutions) in 2020. This study assesses the effectiveness of MISHEQA from multiple stakeholder perspectives using the Technology Acceptance Model (TAM), examining how perceived usefulness and ease of use influenced user acceptance. A qualitative approach was used, combining in-depth interviews, surveys (82 respondents), and FGD with six HEIs, LLDIKTI officials, and quality assurance experts. Thematic analysis was conducted to identify patterns in user experience and system implementation. Three major findings emerged. First, MISHEQA was seen as useful by institutions in the yellow and red clusters, with the reporting and upload features noted as most beneficial. Second, some features were considered redundant: the IQAS document upload feature overlapped with the PPEPP cycle, and the Research and Community Service feature duplicated tracking already conducted via SINTA. Third, findings highlighted the importance of system integration and reducing redundancy in digital quality assurance tools. This study provided valuable feedback to LLDIKTI VII, contributing to the decision to discontinue MISHEQA, which was later replaced by the nationally managed 'Pelaporan SPMI' application by DIKTI (IQAS reporting application).